2021
DOI: 10.1371/journal.pone.0252206
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of leukopenia during sepsis as a marker of sepsis-defining organ dysfunction

Abstract: Background Although both leukocytosis and leukopenia have been considered Systemic Inflammatory Response Syndrome criteria, leukopenia is not generally considered a normal response to infection. We sought to evaluate the prognostic validity of leukopenia as a sign of sepsis-defining hematological organ dysfunction within the Sepsis-3 framework. We hypothesized that leukopenia is associated with higher risk of mortality than leukocytosis among patients with suspected infection. Methods We performed a retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 17 publications
1
25
0
1
Order By: Relevance
“…Noteworthy, the increase of neutrophils, also known as neutrophilia, can occur in response to a stressor, including physical and emotional stress, as well as smoking [41]. Also, chronic disorders, such as inflammatory bowel disease, rheumatic disease, and hepatitis, as well as congenital disorders, such as Down syndrome, are characterized by baseline neutrophilia [42]. Finally, paraphysiological conditions, such as pregnancy and obesity, could be associated with acute to chronic neutrophilia [43].…”
Section: Neutrophilsmentioning
confidence: 99%
“…Noteworthy, the increase of neutrophils, also known as neutrophilia, can occur in response to a stressor, including physical and emotional stress, as well as smoking [41]. Also, chronic disorders, such as inflammatory bowel disease, rheumatic disease, and hepatitis, as well as congenital disorders, such as Down syndrome, are characterized by baseline neutrophilia [42]. Finally, paraphysiological conditions, such as pregnancy and obesity, could be associated with acute to chronic neutrophilia [43].…”
Section: Neutrophilsmentioning
confidence: 99%
“…Leukocyte level was also an independent predictor of weaning failure in this study, however, by comparing the AUC between MPV and leukocyte count, we concluded that leukocyte was an inferior predictive marker of weaning failure. It is known that sepsis or severe infection could cause either leukocytosis or leukopenia [ 29 ]. Many patients presented a normal leukocyte count.…”
Section: Discussionmentioning
confidence: 99%
“…The deleterious accumulation of neutrophils in the endothelial vasculature of organs leads to collateral tissue damage and, ultimately, multiple-organ failure ( 40 ). Leukopenia, which is probably caused by the over-adhesion of leukocytes to the endothelium, is detrimental to the prognosis of sepsis ( 41 ). In addition, endothelial function is also impaired by the released granules after adhesion and infiltration of leukocytes on the endothelium, which accelerates organ dysfunction ( 42 , 43 ).…”
Section: Discussionmentioning
confidence: 99%